QoS Optimization in Cloud Computing Networks - et.al, Abhikriti Narwal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As an increasing era of virtualization, resources are considered as services. To achieve the efficient utilization of the resources,a proper Scheduling and Load balancing technique is required on the Cloud Network. Quality of service parameters plays a vital role in achieving this good goal of utilization. Different load balancing and scheduling strategies of cloud computing studies held to survey QoS optimization. This paper aims at QoS efficiency to develop scheduling and load balancing algorithms to achieve optimization in the cloud networks. This paper briefly talks about the computing model concepts and QoS optimization study executed in various algorithms.In this paper, the performance optimization comparison of improvised algorithms CBSA_LB, EMOSA, and EMOSA_LB with base algorithms MOSA and CBSA has been carried out. The results show that the improvised version has significantly improved the optimization percentage of all performance parameters.